2001
DOI: 10.1046/j.1440-1797.2001.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between increased interdialytic body weight and left ventricular hypertrophy in maintenance dialysis patients

Abstract: SUMMARY: Interdialytic weight gain (IDWG) has been reported to contribute to cardiovascular mortality in haemodialysis patients. In order to determine the relationship of IDWG to the pre‐dialysis blood pressure and left ventricular hypertrophy, 168 patients on maintenance haemodialysis were initially evaluated. The IDWG was estimated as the current pre‐dialysis weight minus the preceding post‐dialytic weight and expressed as a proportion (%) of the current dry weight. Patients were divided into two groups: gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…We used the 3% value; therefore, the results were considered to lack similarity with 5% of findings. Our study showed no correlation between LVMI and IDWG; this finding is consistent with those from the previous study [32]. There are no quality of life comparisons with IDWG in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We used the 3% value; therefore, the results were considered to lack similarity with 5% of findings. Our study showed no correlation between LVMI and IDWG; this finding is consistent with those from the previous study [32]. There are no quality of life comparisons with IDWG in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant difference between the groups with respect to LVH. In a different study, LVH was observed to be significantly high in patients with an IDWG >5%; IDWG was reported to potentially cause LVH via non-blood pressure-mediated mechanisms [32]. We used the 3% value; therefore, the results were considered to lack similarity with 5% of findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study shows that there is no difference in the nutrition index and uraemic toxin removal index between depressive subjects and normal subjects. Therefore, for patients undergoing good‐quality dialysis treatment, 30 physical conditions do not seem to play a role in their depression, and it appears as if psychosocial elements must be studied to a greater extent in order to understand depression in chronic haemodialysed patients.…”
Section: Discussionmentioning
confidence: 99%